Differential shooting training in youth basketball players: an analysis of performance effects - Burkaitė, Grėta; Figueira, Bruno; Schöllhorn, Wolfgang; Coutinho, Diogo; Paulauskas, Rūtenis (Frontiers in Psychology, 2025)
IntroductionDifferential Learning introduces increased variability during practice to enhance motor skill acquisition.MethodsThis study investigated the effects of Differential Training (DT) (Differential Training Group (DTG): n = 19, age = 13.1 ± 0.19 years, height = 170.1 ± 9.5 cm, body mass = 56.9 ± 9.7 kg, training experience = 6.4 ± 1.3 years, maturity offset = 0.7 ± 0.8 years) on shooting accuracy and 1 × 1 small-sided game performance, compared to Traditional Training (TT) [Traditional Training Group (TTG): n = 18, age = 13.8 ± 1.1 years, height = 171.3 ± 8.6 cm, body mass = 59.4 ± 15.4 kg, training experience = 6.5 ± 1.5 years, maturity offset = 0.5 ± 1.1 years], in youth basketball players for an 8-week intervention (16 sessions). Outcomes included 2-point (2-pts) and 3-point (3-pts) shooting accuracy test (BJSAT), 1 × 1 scoring performance, stationary shooting accuracy test (SSAT), and rate of perceived exertion (RPE).ResultsLinear mixed-model analyses revealed that DT improved two-point BJSAT relative to TT at post-test (β = −2.48; p = 0.042) and gains were maintained at retention (p = 0.001). Three-point BJSAT improved over time in both groups (p = 0.004) with no between-group difference at retention. 1 × 1 SSG scoring increased over time (p < 0.001) with no between-group effect at retention. DT outperformed TT in the 30-shot task (Δ = 3.11, 95% CI [1.59, 4.63]; p < 0.001) and elicited lower RPE (Δ = −0.96, 95% CI [−1.47, −0.46]; p < 0.001).DiscussionThese results indicate a superior efficacy of DT for improving shooting performance and managing perceived effort. The differential adaptation rates between mid- and long-range shooting highlight the value of movement variability in skill learning. However, limited transfer to SSG outcomes suggests further research is needed to optimize DT protocols for complex game contexts.